Invasions changing marine biodiversity. Comment on J.M. Pandolfi & C.E. Lovelock Perspective in Ecology "Novelty Trumps Loss in Global Biodiversity" (18 April, 344, 266). - Barreiros, João P. (2014)
Although global biodiversity is declining, local ecosystems are not systematically losing diversity, but rather experiencing rapid turnover in species.